The Critical Power of an Expanded Concept of Moral Injury - Kellison, Rosemary B. ca. 21. Jh. (Journal of religious ethics, 2021)
Contemporary analyses of moral injury in war focus on its occurrence in American veterans who commit or witness acts contrary to their deeply held moral beliefs. Moral injuries suffered by noncombatants are largely absent from this discourse. I advocate for greater inclusion of the victim-centered perspective in studies of moral injury in war. This perspective conceptualizes moral injury as the specific harm suffered when one's moral humanity is not recognized. Given that susceptibility to moral injury is part of moral personhood, failure to acknowledge noncombatants' moral injury represents failure to recognize their full and particular personhood and thus may inflict further moral injury. Centering noncombatants' moral injury strengthens the critical power of moral injury, enabling the identification of specific steps toward establishing just relationships and social trust to repair and prevent moral injury in noncombatants and combatants alike.